Differential Expression of Signaling Pathway Genes Associated With Aflatoxin Reduction Quantitative Trait Loci in Maize (Zea mays L.) - Parish, Felicia; Williams, W. Paul; Windham, Gary L.; Shan, Xueyan (Frontiers in Microbiology, 2019)
The roles of signaling pathway genes related to the aflatoxin reduction trait in maize were studied for the improvement of maize resistance to the fungal pathogen Aspergillus flavus (A. flavus). In this study, 55 maize genes in plant–pathogen interaction signaling pathways were investigated among 12 maize near-isogenic lines (NILs) that carry maize quantitative trait loci (QTL) associated with aflatoxin reduction. These maize NILs were developed from maize inbred lines Mp313E (resistant donor parent) and Va35 (susceptible recurrent parent). The quantitative RT-PCR (qRT-PCR) technique was used to study the gene expression patterns. Seven calcium-dependent protein kinases and one respiratory burst oxidase displayed significant differential expression levels among the maize QTL-NILs. In addition, the gene expression profiles of WRKY transcription factors were also examined. Maize WRKY 52, WRKY 71, and WRKY83 genes displayed significantly differential expression levels among the QTL-NILs. The elucidation of differentially expressed signaling pathway genes involving maize resistance to A. flavus can provide insights into maize disease resistance and enhance maize molecular breeding.